Witnessing Christ: Contextual and Interconfessional Perspectives on Christology - Vellguth, Klaus; Jahnel, Claudia; Biehl, Michael; Teuchert, Lisanne; Mong, Ambrose; Béré, Paul; Reimer, Johannes; George, Samuel; Consuelo Velez Caro, Olga; Sebastian, J. Jayakiran; Buchholz, Dana; Malakyan, Petros G.; et al. (Towards an Ecumenical Missiology, 2020)
How do Christological Perspectives differ and which specific ways of witnessing Christ exist depending on cultural, geographical and confessional context in which they developed? Theologians from Africa, Asia, the Americas, the Middle East, Oceania and Europe discuss these questions focussing on the missiological implications of various contextual Christologies. They aim to answer the question if contextual and confessional provenience coins the epistemological preconditions in a way that creates, shapes and secures peculiar identities.